We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
143
1
avatar+322 

sqrt(9-x^2) ,      x = 3 sin(theta)

 Oct 24, 2018
 #1
avatar+100571 
+2

sqrt ( 9 - [ 3 sin θ ]^2 )    =

 

sqrt  ( 9  -  9sin^2 θ )  =

 

sqrt [  9 ( 1 - sin^2 θ ) ]  =

 

sqrt ( 9 * cos^2  θ )  =

 

sqrt (9)  *  sqrt ( cos^2 θ )  =

 

3 cos θ

 

cool cool cool

 Oct 24, 2018

8 Online Users